2008
DOI: 10.3727/154427208785899966
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Tourism Stakeholders in the Development of Climate Change Decision-Support Tools: A Case Study from Michigan, USA

Abstract: Projection of the potential impacts of climate variability and change on tourism destinations is heavily dependent on the ability to first model present-day relationships between tourism activity and weather conditions. However, current understanding of these relationships is often based more on assumption and anecdotal evidence than hard empirical data. In particular, models that function at the same fine temporal and spatial scales as variations in weather characteristics typically occur are especially lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Due to the latest scientific and politic reactions and to late evolving trends regarding tourism climate change relation more and more studies are approaching now the stakeholder attitudes and reactions on the issue. They are considered a key element for adaptation of recreational industry to the now uncontested climate change problem (Bicknell & McManus 2006;Nicholls & Holecek, 2008;Turton, Dickson, Hadwen, Jorgensen, Pham, Simmons, Tremblay & Wilson, 2010;Charara, Cashman, Bonnell & Gehr, 2011in Becken, 2013Trawoger, 2014, in press) as "the key players' awareness of climate change may determine whether effective action is taken" (Belle & Bramwell, 2005;Klint, Jiang, Law, De Lacy, Filep, Calgaro, Dominey-Howes & Harrison, 2012in Trawoger, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Due to the latest scientific and politic reactions and to late evolving trends regarding tourism climate change relation more and more studies are approaching now the stakeholder attitudes and reactions on the issue. They are considered a key element for adaptation of recreational industry to the now uncontested climate change problem (Bicknell & McManus 2006;Nicholls & Holecek, 2008;Turton, Dickson, Hadwen, Jorgensen, Pham, Simmons, Tremblay & Wilson, 2010;Charara, Cashman, Bonnell & Gehr, 2011in Becken, 2013Trawoger, 2014, in press) as "the key players' awareness of climate change may determine whether effective action is taken" (Belle & Bramwell, 2005;Klint, Jiang, Law, De Lacy, Filep, Calgaro, Dominey-Howes & Harrison, 2012in Trawoger, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study of Australian tourism operators found that although many were concerned about climate change, few had clear plans for adapting (Turton et al 2010 ). Nevertheless, engaging businesses in climate change responses is essential (Chin et al 2019b ; Nicholls and Holecek 2008 ). Most companies will face changes in business costs.…”
Section: Discussionmentioning
confidence: 99%
“…Indianapolis, the state capital and largest city, is a primary attraction for the state's central region, and rolling hills and forests characterize southern Indiana. The IOTD (Newman 2017) has categorized Indiana's tourism products and experiences as follows: culinary and agritourism, heritage and festivals, arts and culture, and outdoor recreation and sport. Indiana promotes culinary tourism, leveraging both a vibrant restaurant scene in the capital (Indianapolis) and throughout the state, with a focus on fresh, local ingredients.…”
Section: Tourism In Indianamentioning
confidence: 99%
“…However, since research in Finland and in other areas has shown that small tourism businesses tend not to identify climate change as a particularly significant or relevant issue, especially given its long-term nature, the large amount of uncertainty associated with climate change science, and the volume of technical jargon employed by climate change specialists (Nicholls & Holecek, 2008;Saarinen & Tervo, 2006), a concerted effort by the appropriate economic development agencies and authorities, to raise awareness and understanding of these opportunities among rural tourism enterprises, is of critical importance. Similarly, the lack of a longer term planning horizon typical of most rural-based tourism enterprises, as noted by, e.g., Nicholls and Holecek (2008) and Rauken and Kelman (2012), represents a substantial obstacle to the most effective and efficient responses to the positive prospects that climate change potentially provides. Hall, Müller and Saarinen (2009) note the strong tradition of state involvement in regional development in the Nordic nations, as well as the importance assigned to tourism as a key element of the development mix in rural and peripheral Nordic regions; the presence of a stronger-than-average support network, in terms of these national-level rural development policies and the availability of assistance to rural regions, is a positive sign with regards to the potential for effectual adaptation.…”
Section: Discussionmentioning
confidence: 99%